2013
DOI: 10.17221/154/2012-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Low-pressure treatment to control food-infesting pests (Tribolium castaneum, Sitophilus granarius) using a vacuum packing machine

Abstract: Kučerová Z., Kýhos K., Aulický R., Stejskal V. (2013): Low-pressure treatment to control food-infesting pests (Tribolium castaneum, Sitophilus granarius) using a vacuum packing machine. Czech J. Food Sci., 31: 94-98.Since recently, the food industry has been faced with serious problems regarding pest-infested food commodities and deregistration of many chemical biocides by the EU Biocide Directive. These conditions have created an urgent need for a physical method of protecting food against pests. Therefore, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
(9 reference statements)
0
10
0
Order By: Relevance
“…Empty stores and mills can be fumigated with hydrogen cyanide (HCN), which is the only fumigant produced in the Czech Republic . Although research activities in this field have only been initiated (Aulicky et al 2012;Kucerova et al 2013), very limited storage techniques based on modified atmospheres (e.g. CO 2 , N 2 , O 2 absorbers, vacuum) are currently used by seed companies for seed protection in the CR in practice.…”
Section: Current Strategies and Methods To Control Pests Of Stored Sementioning
confidence: 99%
See 1 more Smart Citation
“…Empty stores and mills can be fumigated with hydrogen cyanide (HCN), which is the only fumigant produced in the Czech Republic . Although research activities in this field have only been initiated (Aulicky et al 2012;Kucerova et al 2013), very limited storage techniques based on modified atmospheres (e.g. CO 2 , N 2 , O 2 absorbers, vacuum) are currently used by seed companies for seed protection in the CR in practice.…”
Section: Current Strategies and Methods To Control Pests Of Stored Sementioning
confidence: 99%
“…They found that 100% nitrogen caused 100% imago mortality after 33 h; LT 50 = 8.88 h. Zdarkova and Voracek (1993) estimated that mites from the family Acaridae were killed by a low pressure of 95 mm Hg after an exposure of 48 hours. Kucerova et al (2013Kucerova et al ( , 2014 used a vacuum packing machine for laboratory testing of the effectiveness of vacuum packaging on the mortality of 2 species of grain infesting beetle-pests (T. castaneum, S. granarius) at different temperatures and exposure times. There were significant differences between the adult insects of the tested species in their susceptibility to low pressure (vacuum): T. castaneum was approximately 10 times more susceptible to low pressure than S. granarius.…”
Section: Research On Seed Pest Controlmentioning
confidence: 99%
“…Insectresistant packaging is a cheap and efficient measure for the long-term control of pests that attack processed food products (Riudavets et al 2009;Kucerova et al 2013Kucerova et al , 2014Stejskal et al 2017). However, MAPs are employed for the protection of small quantities of commodities, mainly for overthe-counter food packages or small hermetic bags at farms.…”
mentioning
confidence: 99%
“…Large quantities of commodities (approximately 1 t or more) are usually protected in various types of MA/CA cocoons or bubbles (Finkelman et al 2003). Modern multilayer or composite packages liners (e.g., composite aluminium and polyethylene airtight film; Kucerova et al 2013) enable small packages and cocoons to be reasonably and cheaply transportable into a warm environment to enhance the efficacy of CA. From the technical and economic perspective, the most difficult MA/CA method is its application in silos or flat warehouses as the storage must be constructed to be gas-tight or requires permanent CA saturation.…”
mentioning
confidence: 99%
“…As noted by Ciesla and Ducom (2010), the pest control chemicals are becoming difficult to use in mills because many insecticides (i.e., methyl bromide) have been phased out as biocides in Europe. Promising alternatives, such as modified atmospheres and aerosols, are in minor use (Arthur 2012;Kucerova et al 2013Kucerova et al , 2014. However, fumigants are still key elements of the pest control in mills.…”
mentioning
confidence: 99%